Una meditación sobre los símbolos - Belaunde Moreyra, Antonio (Mercurio Peruano, 2020)
This article will try to explain the significance of the national symbols while they express the identity and the national character. The text is divided in six sections: the rainbow incásico, as expression of a natural symbolism; Miranda’s flag, interpreted as a plastically summarized version of the Inca rainbow; two-colored red and white, understood as blood and soul of a country’s crucible of races; the shield that reflects the influence of fisiocratic ideas, of platonic root, in force already from the epoch of the Viceroy Jáuregui; the sun (the national currency), thermometer of the socio-economic health; and the anthem, expression of national enthusiasm.